STRATEGI HUMAS BADAN PENGAWASAN PEMILU KOTA PEKANBARU DALAM MENGOPTIMALKAN PENGELOLAAN MEDIA INFORMASI - ', Oktaviandi; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The existence of Public Relations is certainly very much needed by supervisory agencies, especially the Pekanbaru Regency/City Bawaslu. This is because public relations practitioners do not only manage inter-agency relations but rather trust information in the eyes of the public. The existence of Public Relations in an institution is certainly very helpful in supporting this image to show it to the public in order to convince and increase the credibility of the institution. The aim of the research is to find out Bawaslu's Public Relations Planning in Optimizing the Management of Election Information Media in Pekanbaru City and to find out the Implementation of Bawaslu's Public Relations in Optimizing Election Information Media Management in Pekanbaru City. The type in this research is field research using a qualitative descriptive approach. This research was obtained through observation, in-depth interviews and documentation with five informants selected using purposive techniques, namely the chairman of Bawaslu, Bawaslu public relations officer, and representatives of the supervisory sub-section of the election supervision body. The analysis techniques used are interviews, documentation and triangulation by carrying out data reduction, namely the data obtained in the field is summarized by selecting the main things and arranged systematically so that it is easy to control. Pekanbaru City Bawaslu Public Relations planning for the election by Pekanbaru City Bawaslu, the planning carried out during the election went smoothly and carried out its duties in accordance with Law No. 7 of 2017. Pekanbaru City Bawaslu Public Relations has carried out supervisory duties and authority in stages at each stage implementation of elections, both in the field of prevention, action against violations, whether administrative violations, criminal violations, or violations of the code of ethics in the implementation of general elections. Pekanbaru City Bawaslu's Public Relations strategy is to always provide accurate and reliable information, apart from internet media publications, Bawaslu's Public Relations also utilizes Public Information Management and Services and utilizes print media, such as bunner, flayer and foster. Program evaluation The Election Supervisory Body needs to conduct a program evaluation to identify strengths, weaknesses and strategic steps for the future. Keywords: Communication Planning, Information Management, Bawaslu City Of Pekanbaru